The Invisible Poor : A Portrait of Rural Poverty in Argentina - World Bank (World Bank, 2012)
Many of the poorest Argentines are invisible in official statistics. Four million rural residents and another 12 million in small urban areas lie outside the reach of the Permanent Household Survey (EPH), which is the basis for poverty figures and most data on social conditions in the country. According to the best estimate, roughly a third of rural residents, more than a million people, live in poverty. The urban bias common too many countries have been accentuated by the lack of data on the rural poor. With little information on their condition, it is exceedingly difficult for policy makers to design policies and programs to help move people out of poverty. The report is organized as follows: chapter one profiles rural poverty base on the limited existing data, including the first in-depth analysis of rural poverty ever conducted with the 2001 population census. Chapter two presents findings from the new qualitative study of the rural poor conducted in the first half of 2007. Finally, chapter three concludes with a discussion of methodology for rural poverty analysis, focusing on the issues related to expanding the EPH to full national coverage.